Microglia dynamics in retinitis pigmentosa model: formation of fundus whitening and autofluorescence as an indicator of activity of retinal degeneration - Kenichi Makabe (Nature Portfolio, 2020)
Abstract In patients with retinitis pigmentosa (RP), color fundus photography and fundus autofluorescence (FAF) have been used to estimate the disease progression. To understand the origin and the diagnostic interpretation of the fundus color and FAF, we performed in vivo imaging of fundus color and FAF together with histological analyses of the retinal degeneration process using the RP model mice, rd10. FAF partly represented the accumulation of microglia in the photoreceptor outer segments. Fundus whitening suggested the presence of apoptotic cells, which spatiotemporally preceded increase in FAF. We observed two patterns of FAF localization, arcuate and diffuse, each indicating different pattern of apoptosis, wavy and diffuse, respectively. Diffuse pattern of apoptosis was suppressed in dark-raised rd10 mice, in which outer nuclear layer (ONL) loss was significantly suppressed. The occupancy of FAF correlated with the thinning rate of the ONL. Fractalkine, a microglia chemotactic factor, was detected in apoptotic photoreceptors, suggesting chemokine-induced recruitment of microglia into the ONL, which paralleled with accelerated ONL loss and increased FAF occupancy. Thus, we propose that the degree of photoreceptor apoptosis and the rate of ONL thinning in RP patients might be read from the fundus color and the FAF.